Contractor shop drawing of davit arm roof plan for BRACU (RFA-001_Rev.A,C & E) - Fabcons Construction & Fabrication (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF and DWG version of drawings.